Experimental examination of EFL and MATX eukaryotic horizontal gene transfers: co-existence of mutually exclusive transcripts predates functional rescue - Růžička, Petr (Jihočeská univerzita, 2011)
Many eukaryotic genes do not follow simple vertical inheritance. Elongation factor 1? (EF-1?) and methionine adenosyl transferase (MAT) are enzymes with complicated evolutionary histories and, interestingly, the two cases have several features in common. These essential enzymes occur as two relatively divergent paralogs (EF-1?/EFL, MAT/MATX) that have patchy distributions in eukaryotic lineages that are nearly mutually exclusive. To explain such distributions, we must invoke either multiple eukaryote-to-eukaryote horizontal gene transfers (HGTs) followed by functional replacement, or presence of both paralogs in the common ancestor followed by longterm co-existence and differential losses in various eukaryotic lineages. To understand the evolution of these paralogs, we have performed in vivo experiments in Trypanosoma brucei addressing the consequences of long-term co-expression and functional replacement. In the first experiment of its kind, we have demonstrated that EF-1? and MAT can be simultaneously expressed with EFL and MATX, respectively, without affecting the growth of the flagellates. After the endogenous MAT or EF-1? was down-regulated by RNA interference, MATX immediately substituted for its paralog, while EFL was not able to substitute for EF-1?, leading to mortality. We conclude that MATX is naturally capable of evolving patchy paralog distribution via HGTs and/or long term co-expression and differential losses. The capability of EFL to spread by HGT is lower and so the patchy distribution of EF-1?/EFL paralogs was probably shaped mainly by deep paralogy followed by long term co-existence and differential losses.
Experimental examination of EFL and MATX eukaryotic horizontal gene transfers: co-existence of mutually exclusive transcripts predates functional rescue
Keywords: EFL; MATX; horizontal gene transfer; functional rescue; RNAi; Trypanosoma; EFL; MATX; horizontal gene transfer; functional rescue; RNAi; Trypanosoma